Characterization of special oxidic anticorrosive pigments by XRD and XFR analysis - Ryšánek, Petr; Antoš, Petr; Kalendová, Andréa (University of Pardubice, 2013)
Spinel type pigments were analyzed by X-ray fluorescence spectrometry and X-ray powder diffraction. X-ray fluorescence spectrometry determined the contents of specific elements and X-ray diffraction determined the crystalline structure of the samples. Three samples of spinel pigments were analyzed as such and after their application to aluminum and carbon core. The results of XRD showed the presence of crystalline phase of the pigment and also small amount of Fe2O3 and also the diffraction lines of the cores. The XRF analysis showed the presence of the elements from which were the pigments prepared and also trace amounts of impurities (P2O5, SO3).